Les théâtres à ciel ouvert de Ouagadougou - Karolina Svobodova (EchoGéo)
The city of Ouagadougou is internationally renowned for its cultural dynamism. Thanks to major festivals in the fields of cinema (Fespaco), handicrafts (SIAO) and theatre (Les Récréâtrales), it attracts artists, experts, and tourists every year. But these temporary moments of emulation should not overshadow cultural venues with basic equipment and means that host and develop cultural activities on a daily basis, especially theatre. This article focuses on the locations and characteristics of these theatres. It aims to observe the practices and dynamics that these venues generate locally and to underline the motivations of users for this specific leisure activity. The article concludes with the spatial strategies developed by cultural actors to ensure the survival of their activities in a precarious context.